Rice phytochelatin synthases OsPCS1 and OsPCS2 make different contributions to cadmium and arsenic tolerance. (9th January 2018) - Yamazaki, Shinichi; Ueda, Yosuke; Mukai, Aya; Ochiai, Kumiko; Matoh, Toru
Abstract: Cadmium (Cd) and arsenic (As) pollution in paddy soil and their accumulation in rice ( Oryza sativa ) pose serious threats to human health. Rice internally detoxifies these toxic metal and metalloid to some extent, resulting in their accumulation within the edible parts. However, the mechanisms of Cd and As detoxification in rice have been poorly elucidated. Plants synthesize thiol‐rich metal‐chelating peptides, termed phytochelatins (PCs). We characterized rice PC synthase (PCS) and investigated its contribution to Cd and As tolerance in rice. We identified two PCS homolog genes, OsPCS1 and OsPCS2, in the rice genome. The expression of OsPCS1 was upregulated by As(III) stress in the roots but that of OsPCS2 was not significantly affected. The expression level of OsPCS2 was higher than that of OsPCS1 in the shoots and roots. Recombinant OsPCS1 and OsPCS2 proteins differed in their metal activation. OsPCS1 was more strongly activated by As(III) than by Cd; however, OsPCS2 was more strongly activated by Cd than by As(III). Genetically engineered plants having their OsPCS2 expression silenced via RNA interference ( OsPCS2 RNAi) contained less PCs and more glutathione (GSH), a substrate of PC synthesis, than wild‐type plants, although there was no significant difference in OsPCS1 RNAi plants. OsPCS2 RNAi plants were sensitive to As(III) stress, but Cd tolerance was little affected. On the other hand, treatment with buthionine sulfoximine, an inhibitor of GSH biosynthesis, significantly decreased Cd and As tolerance of rice seedlings. These findings indicate that OsPCS2 is a major isozyme controlling PC synthesis, and that PCs are important for As tolerance in rice. However, PC synthesis may make a smaller contribution to Cd tolerance in rice, and GSH plays crucial roles, not only as a substrate of PC synthesis.